Chambers, Sarah C. From Subjects to Citizens. Honor, Gender, and Politics in Arequipa, Peru 1780-1854. Pennsylvania: The Pennsylvania State University Press, 1999, 286 pp. - Ragas, José (2000)
No presenta resumen